Autocuidado domiciliario del adulto mayor con diagnóstico de hipertensión arterial de la parroquia La Tingue, cantón Olmedo, provincia de Loja. - Celi Celi, María José (2017)
The objetive of this study is determine the knowledge of elderly people with the diagnosis of arterial hypertension about home care on key dimensions such as feeding, physical activity, harmful habits and adherence to treatment of "La Tingue" parish; for which a management proposal self-care of the elderly people was developed with diagnostic of hypertension, the study was descriptive, qualitative and cross-transversal, with a sample of 65 older adults who meet the criteria of both inclusion and exclusion, with this study the level of self-care of the elderly people became known in the dimensions throughout the study, by applying a questionnaire. The main results were a: 36.92% feeding knows the amount of that salt should be consumed a 49.23% doesn’t change on the diet to improve the quality of life, a 52.31% always eats vegetables, fruits, fiber and a Little fat, regard to exercise a 92.31% always performs physical exercises, a 75.38% walks for 30 minutes a day; harmful habits a 100% know that alcohol is harmful to their health and few of them ingest alcohol, and a 93.85% do not smoke; the treatment adherence with a 58.46% sometimes know the secondary effects of medicines they take, and a 36.92% never replace its treatment for an alternative therapy, therefore management proposal of self-care for elderly people was developed with the disgnostic of hypertension. Key-words: self-care home, elderly people arterial hypertension, feeding, physical activity, harmful habits and adherence to treatment